HUBUNGAN PEMBERIAN ASI EKSKLUSIF DAN PERILAKU MEROKOK KELUARGA DENGAN KEJADIAN PNEUMONIA BALITA - Ni Luh Putu Devi Wardani; Made Rismawan; Putu Ayu Ratna Darmayanti (Jurnal Mutiara Kesehatan Masyarakat, 2022)
Respiratory tract infection caused by bacteria, viruses, and fungi that can attack the respiratory tract of toddlers. The purpose of this study was to identify the correlation between exclusive breastfeeding and family smoking behavior with the pneumonia case on toddlers at the Public Health Center, Marga 1. The study employed an analytic design with a cross-sectional approach, using 219 respondents with parents who had toddlers. Sampling employed simple random sampling. Data collection were questionnaires on exclusive breastfeeding and family smoking behaviour with the pneumonia case. The results of this study found that almost all toddlers who were not given exclusive breastfeeding but experienced pneumonia were 145 respondents (98.6%) and almost all respondents who had families with smoking habits as many as 146 respondents experienced pneumonia (99.3%) with P-value <0.001. In conclusion there was a significant association between the group of non-exclusive breastfeeding toddlers with the incidence of pneumonia and there was a significant relationship between family smoking behavior and the incidence of pneumonia in toddler